2013
DOI: 10.1021/ic401783c
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III) Hydrido N-Heterocyclic Carbene–Phosphine Complexes as Catalysts in Magnetization Transfer Reactions

Abstract: The hyperpolarization (HP) method signal amplification by reversible exchange (SABRE) uses para-hydrogen to sensitize substrate detection by NMR. The catalyst systems [Ir(H)2(IMes)(MeCN)2(R)]BF4 and [Ir(H)2(IMes)(py)2(R)]BF4 [py = pyridine; R = PCy3 or PPh3; IMes = 1,3-bis(2,4,6-trimethylphenyl)imidazol-2-ylidene], which contain both an electron-donating N-heterocyclic carbene and a phosphine, are used here to catalyze SABRE. They react with acetonitrile and pyridine to produce [Ir(H)2(NCMe)(py)(IMes)(PPh3)]BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(134 citation statements)
references
References 39 publications
(83 reference statements)
4
128
0
1
Order By: Relevance
“…Upon replacing the protio form of these NHC ligands with their deuterated variants d 22 ‐IMes7, 22 and d 22 ‐SIMes, the levels of indazole and acetonitrile proton signal enhancements under SABRE changed as detailed in Table 1. For d 22 ‐IMes, the maximum indazole proton signal enhancement was now obtained at 90 G rather than 70 G, and after 35 s of contact with p‐ H 2 , rather than the 20 s used earlier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon replacing the protio form of these NHC ligands with their deuterated variants d 22 ‐IMes7, 22 and d 22 ‐SIMes, the levels of indazole and acetonitrile proton signal enhancements under SABRE changed as detailed in Table 1. For d 22 ‐IMes, the maximum indazole proton signal enhancement was now obtained at 90 G rather than 70 G, and after 35 s of contact with p‐ H 2 , rather than the 20 s used earlier.…”
Section: Resultsmentioning
confidence: 99%
“…The second form of catalyst, 3a , contains three indazole ligands, and now, polarisation transfer is facilitated by magnetic inequivalence effects. The mechanisms of ligand exchange in these types of complex have been examined previously when the substrate is pyridine and underpin the SABRE effect 7, 22. These studies have enabled the hyperpolarisation of acetonitrile and reveal that it is possible to improve the pyridine response when CD 3 CN is used.…”
Section: Introductionmentioning
confidence: 97%
“…For both mechanisms, p-H 2 displaces the COD on the Ir-catalyst and the symmetry of p-H 2 is broken (Scheme 1). At low but non-zero field, such as the polarizing field used in these studies, the interplay between chemical shift evolution and scalar coupling between the hydride protons and the substrate protons create single spin longitudinal z-magnetization [2125,28,29]. The chemical shift interaction between this z-magnetization and zero quantum states introduces a complex field dependency in the polarization of protons of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports of the participation of methanol (MeOH) in the catalytic complex have been reported. Fekete et al [29] confirmed the presence of [Ir(H) 2 (MeOH)(py)(IMes)(PPh 3 )]Cl (py = pyridine; IMes = 1,3-bis(2,4,6-trimethylphenyl)imidazole-2-ylidene) by multinuclear NMR. Eshius et al [32] proposed the presence of [Ir(IMes)(H) 2 (py) 2 (MeOH)]Cl to account for the reduced enhancement observed at trace concentrations while Lloyd et al[36] confirmed the presence of this complex as well as [Ir(IMes)(H) 2 (py) 2 (H 2 O)]Cl at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally SABRE was a low-field method that was used to hyperpolarize various Ir-complexes and substrates [8,9,11,[28][29][30][31]. For this reason, first of all we would like to see whether the stabilized complex can be used for generating hyperpolarization in conventional low-field SABRE experiments (LF-SABRE).…”
Section: H-sabre Field Dependence (Low Field Sabre)mentioning
confidence: 99%